1998
DOI: 10.1073/pnas.95.15.8951
|View full text |Cite
|
Sign up to set email alerts
|

Social inhibition of song imitation among sibling male zebra finches

Abstract: A male zebra finch, Taeniopygia guttata, kept with its father until adulthood develops an imitation of its father's song motif. We report here that the completeness of this imitation was sensitive to the social or auditory context in which the bird grew up: the greater the number of male siblings in a clutch, the shorter the mean duration of the song motif and the fewer the mean number of song notes imitated from the father; the latter shortfall was not compensated by other, improvised notes. We call this effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 20 publications
8
88
1
Order By: Relevance
“…However, in a family setting, where a few siblings are interacting with a single tutor (their father), typically only one of them (the first one to imitate the father's song) will develop an accurate imitation. In the other siblings, song imitation is partially inhibited, resulting in divergence (Tchernichovski and Nottebohm, 1998). This is not due to lack of opportunity to learn from a busy tutor: a recent study showed that the rate at which tutors produced song is inversely related to pupil attention and to song learning (Chen et al, 2016).…”
Section: How Song Learning Sustains Polymorphic Dialectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a family setting, where a few siblings are interacting with a single tutor (their father), typically only one of them (the first one to imitate the father's song) will develop an accurate imitation. In the other siblings, song imitation is partially inhibited, resulting in divergence (Tchernichovski and Nottebohm, 1998). This is not due to lack of opportunity to learn from a busy tutor: a recent study showed that the rate at which tutors produced song is inversely related to pupil attention and to song learning (Chen et al, 2016).…”
Section: How Song Learning Sustains Polymorphic Dialectsmentioning
confidence: 99%
“…But errors in song imitation are not entirely random: the accuracy of song imitation varies with environmental (Nowicki et al, 2002) and social (Chen et al, 2016;Tchernichovski and Nottebohm, 1998) conditions. Furthermore, there is evidence that the accuracy of song imitation may change adaptively -i.e.…”
Section: How Song Learning Sustains Polymorphic Dialectsmentioning
confidence: 99%
“…Songbirds learn their songs by imitating an adult tutor. Imitation increases song similarity within a group, but there are also divergent forces (68) that drive considerable variability in song among individuals; moreover, there are regional dialects among groups of birds from the same species (69). Thus, birds have a song culture that develops over generations.…”
Section: Song Development Over Generations: Evolution Of Song Culturementioning
confidence: 99%
“…Conversely, many songbirds learn their vocalizations directly and indirectly through hearing aggressive, territorial interactions of their fathers and neighboring conspecifics (e.g., Nuttall's white-crowned sparrows, Zonotrichia leucophyrys nuttali, Bell, Trail, & Baptista, 1998;European starlings, Bertin, Hausberger, Henry, & Richard-Yris, 2007;zebra finches, Zann, 1990). In zebra finches, presence and interactions with even male siblings can contribute to features of a male's song (e.g., Tchernichovski, Lints, Mitra, & Nottebohm, 1999;Tchernichovski & Nottebohm, 1998).…”
Section: Heightened Sociality and The Vocal Repertoirementioning
confidence: 99%